2008
DOI: 10.1519/jsc.0b013e31816a5af6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Simulated Karate Sparring Matches in Young Men and Boys

Abstract: The purpose of this study was to investigate the duration of each series of offensive and defensive techniques and the cardiovascular, metabolic, and perceptual responses during 2- and 3-minute bouts of simulated karate sparring. Six young men (age, 18-20 years) and 6 boys (age, 16-17 years) participated in this study. We formed 3 pairs of men and 3 pairs of boys to create a demanding competitive environment. After a rest period, each pair performed a 2-minute bout of sparring, sat quietly for 60 minutes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 16 publications
8
37
0
10
Order By: Relevance
“…In addition to that, it is possible to affirm that karate is characterized as an intermittent modality of moderate to high intensity, according to the illustration in figure 3 (A and B), corroborating previous studies 3,4 and other modalities of martial arts [23][24][25] . Training stimuli from modalities with intermittent characteristics are efficient in promoting the significant increase in O 2max o pre-puberty children 26 , young adults, middle-aged 27 and elderly subjects 28 , of both sexes 27 , regardless of the training level, since the responses in the cardiorespiratory indices include from sedentary subjects to athletes 27,29 .…”
Section: Discussionsupporting
confidence: 90%
“…In addition to that, it is possible to affirm that karate is characterized as an intermittent modality of moderate to high intensity, according to the illustration in figure 3 (A and B), corroborating previous studies 3,4 and other modalities of martial arts [23][24][25] . Training stimuli from modalities with intermittent characteristics are efficient in promoting the significant increase in O 2max o pre-puberty children 26 , young adults, middle-aged 27 and elderly subjects 28 , of both sexes 27 , regardless of the training level, since the responses in the cardiorespiratory indices include from sedentary subjects to athletes 27,29 .…”
Section: Discussionsupporting
confidence: 90%
“…Sometimes cardiovascular demands remained stable through the matches. This result is similar to that reported by another research who observed a small variation in HR in two karate combat simulations, one of 2 min and another of 3 min duration (Bouhlel et al 2006;Lide et al 2008). …”
Section: Discussionsupporting
confidence: 92%
“…Kata represents a pre-arranged form of karate techniques in an exhibitive manner. Kumite means karate sparring, which involves the execution of offensive, defensive and counter-attack techniques against a rival [22,23]. Based on the World Karate Federation rules, an official kumite competition lasts 3 minutes for senior males and 2 minutes for senior females in elementary stages, and then lasts 1 more minute for each of them in the final stages and fight for medals [11].…”
Section: Introductionmentioning
confidence: 99%